Food loss assessment in micro, small and medium-sized agro-industrial enterprises - Campos-Rodríguez, Rooel (2021)
This research emerges from a growing concern to face the problem owing to food loss (FL), with the purpose to evaluate processes in agro-industrial product elaboration, focusing on the determination of food loss critical points (FLCP) to promote their further reduction. The research was carried out in a Costa Rican MSME (micro, small and medium-sized enterprise), dedicated to the processing of tropical fruits. The FL assessment proposed methodology enabled the establishment of a food loss valorization team (FLVT) for a multidisciplinary approach throughout the study, as well as a flowchart construction for the selected process (soursop pulping) and the identification and quantification of losses. The assessment of the food loss points (FLP) was performed using a matrix and a criticality index based on severity and probability of occurrence; which led to the identification of the critical points. As a result, four FLCP were detected; regarding the raw materials input, the pulping operation and the transference of processed pulps into containers. The case study shows that the applied methodology allows to determine FLCP in an MSME such as the studied, as a first action to identify and reduce food loss, improve efficiency and consider further waste management strategies.